2017
DOI: 10.3390/molecules22081334
|View full text |Cite
|
Sign up to set email alerts
|

H2S-Mediated Protein S-Sulfhydration: A Prediction for Its Formation and Regulation

Abstract: Protein S-sulfhydration is a newly discovered post-translational modification of specific cysteine residue(s) in target proteins, which is involved in a broad range of cellular functions and metabolic pathways. By changing local conformation and the final activity of target proteins, S-sulfhydration is believed to mediate most cellular responses initiated by H2S, a novel gasotransmitter. In comparison to protein S-sulfhydration, nitric oxide-mediated protein S-nitrosylation has been extensively investigated, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 72 publications
(131 reference statements)
0
31
0
Order By: Relevance
“…[ 14 ] It regulates the functions of various enzymes in cells, mainly by the modification of cysteine residues to form protein persulfides called S‐sulfhydration. [ 15 ] Previous studies have revealed that high concentration of exogenous H 2 S may induce the specific inhibition of cancer cells via cellular cycle arrest, miRNA regulation, mitochondrial damage, or uncontrolled intracellular acidification owing to the differences in metabolism and signaling pathway between cancer and normal cells. [ 16 ] More importantly, the recent exploration uncovered that H 2 S can regulate CAT activity in some types of plant cells and bacteria, and this effect can be highly varied depending on cell types.…”
Section: Figurementioning
confidence: 99%
“…[ 14 ] It regulates the functions of various enzymes in cells, mainly by the modification of cysteine residues to form protein persulfides called S‐sulfhydration. [ 15 ] Previous studies have revealed that high concentration of exogenous H 2 S may induce the specific inhibition of cancer cells via cellular cycle arrest, miRNA regulation, mitochondrial damage, or uncontrolled intracellular acidification owing to the differences in metabolism and signaling pathway between cancer and normal cells. [ 16 ] More importantly, the recent exploration uncovered that H 2 S can regulate CAT activity in some types of plant cells and bacteria, and this effect can be highly varied depending on cell types.…”
Section: Figurementioning
confidence: 99%
“…To our knowledge, no information exists on the presence of H 2 S in plant or animal peroxisomes. However, proteomic studies of animals and plants have identified catalase as a potential target of persulfidation (Mustafa et al ; Aroca et al ), which is a post‐translational modification (PTM) mediated by H 2 S that modulates the function of target proteins (Iciek et al ; Ju et al ). Thus, this study mainly aims to evaluate the presence of H 2 S in plant peroxisomes and its potential biochemical implications.…”
Section: Introductionmentioning
confidence: 99%
“…It is also well-known that -SH groups of some proteins can undergo reversible polysulfidation that influences their catalytic activity. S-nitrosylation and polysulfidation have similar mechanisms and occurred at acid-base motif [97]. Aside from S-nitrosylation of CaMKII at Cys6, it was recently reported that CaMKII is sensitive to inhibition by RSS through polysulfidation at Cys6, being competitive with ATP [98,99].…”
Section: Discussionmentioning
confidence: 99%